A review on household air pollution and biomass use over Kenya - Shilenje, Zablon Weku; Maloba, Scholastica; Ongoma, Victor (Frontiers in Environmental Science, 2022)
Abstract Household Air Pollution (HAP) causes multiple non communicable diseases such as pneumonia, stroke, and ischaemic heart disease, responsible for over 3.8 million deaths globally per year. How Kenya has high HAP, mainly from solid fuels. This review assesses its effect and identify factors that could be improved with policy in Kenya. A systematic review approach is used, mainly considering 88 articles on the Web of Science, published from 1951 to 2022. We excluded papers on HAP caused by other forms of fuel, subjective study type, and studies focusing on animals. The results show that rural setting and urban slums have more HAP, ventilation is an important factor, HAP high in evening, children and women health significantly affected. There is need for interventions to reduce the use of biomass fuels in Kenya. The interventions include: improved access to efficient cookstoves with ventilation, community health awareness about ventilation, housing rules for better ventilation in rural and urban areas, and NGO partnership for improving access to improved cookstove in rural area. Government role in subsidizing supply and cost of renewable energy, and adoption energy policies that encourage populations to switch to more efficient cookstoves, cleaner energy, and modern bio-fuels.